2016
DOI: 10.18552/2016/scmt4s247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture Content of Wet Fly Ash on Basic Properties of Mortar and Concrete

Abstract: This study is aimed to investigate feasibility of using wet low CaO fly ash as a cement replacing material in concrete. Effect of moisture content of wet fly ash on basic properties of mortar and concrete is studied. The properties of mortar and concrete made with the wet fly ash are investigated and compared with those made with dry fly ash. Wet fly ashes prepared in the laboratory are used in the investigation. Moisture contents of the wet fly ashes are 25%, 45%, and 65%. The wet exposure period of fly ash i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…2. θ hp,c and θ hp,slag are the ratios of minimum water to binder required to obtain maximum reactions of cement and slag, respectively. The values of θ hp,c and θ hp,slag are 0.21 and 0.30, obtained from previous studies [1,7]. W wgel (t) is defined as the weight of water entrapped in products of hydration and can be calculated from Eq.…”
Section: Composite Materials and Materials Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…2. θ hp,c and θ hp,slag are the ratios of minimum water to binder required to obtain maximum reactions of cement and slag, respectively. The values of θ hp,c and θ hp,slag are 0.21 and 0.30, obtained from previous studies [1,7]. W wgel (t) is defined as the weight of water entrapped in products of hydration and can be calculated from Eq.…”
Section: Composite Materials and Materials Engineeringmentioning
confidence: 99%
“…A previous study reported that specific heat of concrete at a given time can be calculated based on weight fraction of each constituent and their specific heat values [6]. As the specific heat of water is the highest among all the constituents, specific heat of concrete is highly dependent on the free water content [7]. Transient technique provides accurate results for specific heat of hardening cement paste [3].…”
Section: Introductionmentioning
confidence: 99%